A Spline Method based on the Crack Induced Deflection for Bridge Damage Detection. (November 2020) - Mousavi, Mohsen; Holloway, Damien; Olivier, J.C.; Gandomi, Amir H.
Highlights: A new damage detection method based on the integral of crack induced deflection is proposed. A Qausi-static moving mass is used to excite a simply supported beam with road roughness. The beam deflection at each time instance measured at limited points is interpolated. An equation for calculation of the severity of crack damage is obtained. The method can accurately detect the crack location and severity at the presence of 100% noise. Abstract: This paper proposes a novel method for damage detection on a simply supported beam subjected to a moving mass using multiple vibration data measured from a vehicle-bridge interaction (VBI) model. It is shown first that the integral of the difference between the deflection time history of the healthy and damaged beam reaches a local maximum at the location of the crack. As such, the integral of the difference between the vibration time history of the healthy and damaged beam at some dense points on the beam is required. However, practically the number of measured points is limited. Therefore, the data from VBI measured at a limited set of points have been interpolated at each time instant to estimate the deflection of other locations on the beam. It has been demonstrated through several simulations that the proposed method can detect both the location and severity of damage on the beam while considering the interaction between the moving mass and the bridge, as well as the effect of road roughness. It is also shown that the proposed method is fairly robust to noise in both damage localisation and quantification.